Daily mindfulness is associated with recovery processes among coaches—a 4-week diary study - Pawsey, F.; Wong, J. H. K.; Kenttä, G.; Näswall, K. (International Sport Coaching Journal, 2021)
Sport coaching is a profession that is often demanding and one in which psychological burnout is problematic. Recovery from work demands is known to be important in preventing burnout, but research has paid little attention to short-term recovery for coaches. The present study therefore focused on day-to-day recovery. Specifically, the authors investigated the role of mindfulness in recovery, given previously established empirical relationships between mindfulness and recovery processes. The authors used an intensive diary study design to gather daily data from a sample of 46 sport coaches, over a period of 28 consecutive days. Multilevel modeling allowed data analysis at the intraindividual level, providing insights into daily recovery processes for individual coaches. The results showed that increases in daily mindfulness, relative to coaches` individual mean levels, were predictive of higher levels of recovery-related variables (energy and mood) through mechanisms of reduced rumination and improved sleep. The present study highlights mindfulness as a potential path to daily recovery and the prevention of burnout among coaches. The study lays groundwork for the investigation of mindfulness training as a recovery-promoting intervention for coaches, potentially through easily accessible means, such as app-based training delivery and the incorporation of informal mindfulness practice into daily activities.